FRI0012 Imbalance between histone acetyl transferase and histone deacteylase activities and modulation of hdac activity and tnfa production by hdac inhibitors in patients with ankylosing spondylitis or rheumatoid arthritis. (23rd January 2014) - Toussirot, E.; Abbas, W.; Khan, K. A.; Tissot, M.; Jeudy, A.; Baud, L.; Bertolini, E.; Wendling, D.; Herbein, G.
Abstract : Background: TNFa is a major cytokine involved in conditions such as ankylosing spondylitis (AS) and rheumatoid arthritis (RA). Epigenetic regulation corresponds to different processes including modifications in histone proteins. These mechanisms regulate the transcription of genes coding for inflammatory cytokines such as TNFa. The acetylation of histone proteins (dependent on histone acetyl transferase-HAT-) promotes gene transcription while deacetylation (controlled by histone deacetylase) prevents this reaction. Limited data are available on HAT and HDAC activities in AS or RA. HDAC inhibitors (HDACi) are currently in development and may be of interest in modulating TNFa production in RA or AS. Objectives: To determine the levels of HAT and HDAC activities in patients with AS or RA compared to healthy controls (HC) and to evaluate the ex vivo effects of HDACi (trichostatin A-TSA- and sirtinol -Sirt-) on HAT and HDAC activities and TNFa production by PBMC. Methods: 21 patients with AS (New York criteria, 18 M, mean age ± SEM 44.3 ± 3.2 years, disease duration 14.1 ± 2.2 years), 52 patients with RA (ACR 1987 criteria, 16 M, mean age 56.9 ± 1.6, disease duration 11.3 ± 1.2) and 38 healthy controls (HC) (12 M, mean age: 34.6 ± 1.8) were evaluated. No patient received biologics. HAT and HDAC activities were assessed on nuclear extracts of PBMC isolated by Ficoll hypaque using a colorimetric assay (EpiQuick HAT Activity/inhibition Assay kit, and EpiQuick HDAC Activity/inhibition Assay kit, Epigentek). These activities were measured prior and after ex vivo treatment of PBMC by HDAC inhibitors. TNFa was evaluated in PBMC culture supernatants after 1 and 3 days (TNFalpha Quantikine ELISA kit, R&D Systems). Results: HAT activity was decreased in patients with AS compared to HC (68.2 ± 8.1 vs 111.3 ± 15.5 ng/h/mg) (p= 0.05) while RA patients had increased HAT activity (126.8 ± 16.4 vs 111.3 ± 15.5 ng/h/mg; NS). Compared to HC, HDAC activity was decreased in both AS (p= 0.01) and RA (NS) (HC vs AS vs RA: 4778.9 ± 752 vs 1984. 6 ± 249 vs 3915.9 ± 790 pmol/min/mg). No correlation was observed between clinical disease assessment in RA or AS and HAT or HDAC activity. Ex vivo addition of TSA or Sirt to PBMC reduced HDAC activity by 51.1% in HC and by 37.7% in RA but had no effect in AS.HAT activity was not modulated by HDACi. TNFa production by PBMC was down regulated by the addition of TSA or Sirt to cell culture in HC and RA but this regulation was only obtained with Sirt in PBMC culture from patients with AS. Conclusions: HAT and HDAC activities are dysregulated in AS and RA with a balance between HDAC and HAT favoring HAT activity and promoting gene transcription. Ex vivo treatment of PBMC by HDAC inhibitors may regulate HDAC activity and TNFa production especially in HC and RA but seems less effective in AS. Disclosure of Interest: None Declared